EFEKTIVITAS KURIKULUM ENTREPRENEURSHIP PRESIDENT UNIVERSITY TERHADAP ENTREPRENEURAL INTEREST, KNOWLEDGE, DAN ORIENTATION MAHASISWA - Pandu Adi Cakranegara; Johan Krisnanto Runtuk (President University, 2019)
Entrepreneurship education is an important factor to help young people to know and pursue entrepreneurial behavior. Therefore, currently many universities require entrepreneurship education. This study aims to determine the effectiveness of curriculum entrepreneurship at President University towards Entrepreneurial Interest, Knowledge, and Student Orientation. Data was collected through an online questionnaire. A total of 219 students were sampled. Based on the results of descriptive analysis and multiple linear regression analysis, it was found that curriculum entrepreneurship applied at President University had a positive influence on Entrepreneurial Interest, Knowledge, and Student Orientation.